Increasing polio immunization coverage through outreach services - Ekayanti, Ekayanti (Journal of Evidence-Based Community Health, 2024)
Polio vaccination is a vaccine that protects children from polio. The purpose of this service is to increase public awareness and understanding of the importance of immunization, to create a healthier future for our children through education on polio vaccination. The results of the evaluation related to the provision of materials that have been delivered found that 85% of parents agreed that their children were given polio vaccination. Participants who were given Polio immunization were 56 out of 74 toddlers and 14 others were absent, 4 of whom were parents who did not agree that their children were vaccinated on the grounds that their children were not healthy